Bayan Traditional Library as the Source of Information, Education, and Cultural Preservation - Bonang, Dahlia; Fitriyah, Any Tsalasatul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
This case study is aimed at exploring the development and role of Bayan traditional library as the source of information, education, and cultural preservation. The data were gathered through observation, interviews, and documentation. The study engaged traditional leaders, library managers, and Pokdarwis (tourism awareness group) as the informants. The study showed that Bayan traditional library was present among indigenous peoples due to the modernization which shifted the younger generation's paradigm to continue preserving culture. The library functions are as a forum to foster public interest in reading, a vehicle for Bayan traditional museum, and facilities for Bayan community to meet the book needs related to formal and informal education. It also provided numerous references for researchers to conduct research, learning facilities for local wisdom, and the arts of the native community. The library services are of course still conventional, as it can be seen from the concept of open library space, and circulation services are not organized technologically. Moreover, the role of the library in preserving culture is carried out by documenting various cultural activities, which are then translated into writings or works to increase the spirit of the younger generation to maintain cultural existence.